Pais surdos e filhos ouvintes - Rezende, Julia de Araujo (2016)
The work presented here studies the relationship between deaf parents and their hearing children, also called CODA (Children of Deaf Adults). First a reflection about deafness and the role of the family in society and the members who compose it was made in order to understand how families and families of the deaf are organized. It was also analyzed the relationship between parents and their children. It was accomplished an analysis of the interviews with CODAs of in order to interpret their daily lives in a sociocultural point of view, ie, questioning the contact with the representation of deafness, the socialization on deaf families, the use of sign language and the appropriation of the meanings shared by the deaf in the sense of symbolic intersections that shape a particular identity. The data suggests that disability per se is not the cause of problems of function in social and family relationships, which could be expected as deafness leads to a pattern of diverse communication between children listeners with their deaf parents. It might be expected that the relationship established between the hearing children with their deaf parents that share two languages and two cultures, could lead to difficulties in the relationship. The report of the CODAs, in this research, shows that some impasses and particularities exist in their relationship with their parents, but these issues do not lead to inadequacies, but to differences that do not mean that relations are broken or compromised